Estradiol/testosterone ratio: unveiling links between hormones, sexual function, and health in chronic non-communicable diseases - María A. Gómez-Gutiérrez; Juan M. Huertas-Cañas; Juan M. Montoya-Osorio; Andrés Bedoya-Ossa (Urología Colombiana)
Objective: Determine the association and utility of measuring estradiol-to-testosterone ratio on erectile dysfunction (ED) and libido. Materials and methods: This is a case–control study involving 32 adult male patients with chronic pathologies who consulted for sexual dysfunction. Cases defined as subjects with hypoactive sexual desire. Results: Diabetes mellitus showed a significant LR of 6.58. Testosterone levels differed between cases and controls, yet no differences emerged for estradiol or estradiol-to-testosterone ratio. Subgroups defined by testosterone and LH levels were established. Low testosterone and inappropriately normal LH showed an OR of 13 and significant LR. Analysis of normal and inappropriately normal LH categories revealed significant differences in E/T ratio and adjusted testosterone. ROC curves assessed E/T ratio effectiveness for diagnosing hypogonadotropic hypogonadism and SD. A cutoff point of 5.98 for E/T ratio yielded 0.85 sensitivity and 0.79 specificity. Conclusions: No significant differences were observed between cases and controls. Differences were observed when analyzed in subgroups based on LH response, indicating estradiol-to-testosterone ratio may be useful in studying inappropriate LH response. A larger sample size is warranted to be able to extrapolate our results.